Faktor-Faktor yang Mempengaruhi Kejadian Asfiksia Neonatorum di Puskesmas Pagar Merbau Kec. Pagar Merbau Kab.Deli Serdang Provinsi Sumatera Utara Tahun 2023 - Riza Umami; Kamelia Sinaga; Imran Saputra Surbakti; Asnita Sinaga; Riza Novianti (NAJ Nursing Applied Journal, 2025)
Asphyxia is a condition in which a baby fails to breathe spontaneously and regularly immediately after birth, preventing oxygen intake and carbonic acid removal (Dewi, 2011). It is a pathological change caused by insufficient oxygen in the respiratory air, leading to hypoxia and hypercapnia (Ridha, 2014). Asphyxia can occur at birth (primary asphyxia) or develop later (secondary asphyxia). This study aims to identify factors influencing neonatal asphyxia at the Pagar Merbau Health Center, Deli Serdang Regency, in 2023. The research employs an analytical method with a cross-sectional approach. Data analysis utilized the chi-square statistical test and Fisher’s Exact Test in SPSS to determine the relationship between independent and dependent variables. Results from bivariate analysis using Fisher's Exact Test revealed a p-value of 0.344, indicating no statistically significant relationship between maternal age and neonatal asphyxia at the Pagar Merbau Health Center in 2023. To reduce neonatal asphyxia risk, pregnant women should undergo regular antenatal care using available health facilities to detect complications such as premature birth (<37 weeks), postmature birth (>42 weeks), low birth weight, or premature rupture of membranes. Early detection and appropriate medical intervention can minimize neonatal asphyxia incidence. Healthcare providers must enhance prenatal education and monitoring programs to ensure better maternal and neonatal health outcomes. Strengthening healthcare services and raising awareness among pregnant women about risk factors can contribute significantly to reducing neonatal asphyxia cases.